2020
DOI: 10.1017/s1460396920000370
|View full text |Cite
|
Sign up to set email alerts
|

An institutional review: dosimetry comparison between simultaneous integrated boost IMRT and VMAT for prostate cancer

Abstract: Purpose: A comparative study was performed about the plan parameters and quality indices between volumetric arc therapy (VMAT) and intensity-modulated radiotherapy (IMRT) for the treatment of high-risk prostate cancer patients. The aim of this retrospective study was to compare the two methods of external beam radiotherapy IMRT and VMAT in terms of plan quality and efficacy. Material and method: Fifteen high-risk prostate patients were planned for radiotherapy using 6 MV photon. Three do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…So, VMAT-1A and VMAT-2A techniques shortened the treatment time delivered by 7F IMRT and 9F IMRT techniques which were more comfortable for the patient and helpful in decreasing the machine workload in a busy department. Our data were compared with those published by (Mukhtar et al 2021 ), who found that VMAT was more efficient and had lesser dose delivery time and MU than IMRT.…”
Section: Discussionmentioning
confidence: 80%
“…So, VMAT-1A and VMAT-2A techniques shortened the treatment time delivered by 7F IMRT and 9F IMRT techniques which were more comfortable for the patient and helpful in decreasing the machine workload in a busy department. Our data were compared with those published by (Mukhtar et al 2021 ), who found that VMAT was more efficient and had lesser dose delivery time and MU than IMRT.…”
Section: Discussionmentioning
confidence: 80%
“…Eclipse version 16.1 and RayStation version 12A were used for MCO-based treatment planning for each included CT dataset with TrueBeam linear accelerator and Millennium multi-leave collimator (Varian Medical Systems, Inc., Palo Alto, CA, USA), 2 full arcs and beam energy of 6 MV photons selected [ 31 , 32 ]. The first and second arcs rotated from 175 to 185 degrees counterclockwise, and from 185 to 175 degrees clockwise, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Table 2 shows the dose/volume treatment objectives used for the MCO-based planning of the two systems as per in-house protocol [ 17 , 33 ]. Rectum D 50% (V 50 ≤ 50%) and PTV 76 D 98% were selected as trade-off criteria because of their conflicting natures [ 17 , 23 ], i.e., when the dose received by at least 50% of the rectal volume decreased for minimizing the adverse effects of prostate RT, the effectiveness of the prostate cancer treatment also decreased as a result of the reduction of dose received by 98% volume of PTV 76 , and vice versa [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…A significantly higher 10-year ST incidence in the pelvis was found in patients using IMRT and VMAT compared with 3D-CRT (10.7% versus 6%). Fifteen high-risk patients with PC treated with 6 MV photon beams were enrolled in the study to compare IMRT and VMAT in terms of plan quality and efficacy [28]. For IMRT, seven fixed beam angles were used, and the dose was optimized using the SW method.…”
Section: Data Comparisonmentioning
confidence: 99%